2019
DOI: 10.23876/j.krcp.18.0114
|View full text |Cite
|
Sign up to set email alerts
|

The role of senescence of bone marrow cells in acute kidney injury

Abstract: Background The prevalence of acute kidney injury (AKI) in elderly patients has grown considerably. Age-associated changes in the immune system can be one of the critical factors determining AKI outcomes. This study aimed to investigate the role of senescence of bone marrow (BM)-derived cells in the development of AKI, focusing on the immune response. Methods Female 7-week-old C57BL/6 mice were irradiated and treated with BM cells from either 48-week-old or 8-week-old ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
3
1
Order By: Relevance
“…In contrast to current data showing persistent inflammation, our group previously demonstrated that young mice who were transplanted with senescent bone marrow (BM) from aged mice demonstrated significantly attenuated kidney inflammation and injury, as compared to aged mice transplanted with BM from young mice 26 . This clear discrepancy in the phenotype of post-ischemic senescent immune cells led us to hypothesize that the intrarenal microenvironment surrounding immune cells might be more important in driving macrophage polarization.…”
Section: Discussioncontrasting
confidence: 72%
“…In contrast to current data showing persistent inflammation, our group previously demonstrated that young mice who were transplanted with senescent bone marrow (BM) from aged mice demonstrated significantly attenuated kidney inflammation and injury, as compared to aged mice transplanted with BM from young mice 26 . This clear discrepancy in the phenotype of post-ischemic senescent immune cells led us to hypothesize that the intrarenal microenvironment surrounding immune cells might be more important in driving macrophage polarization.…”
Section: Discussioncontrasting
confidence: 72%
“…Our study showed an increase in blood cytokine consistent with previous reports [5]. These cytokines might be involved with lung injury.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the incidence and severity of AKI increase with age [21]. AKI is associated with an increased risk of mortality, hospitalization, and other comorbidities, such as cardiovascular events [22]. In addition to acute-phase problems associated with AKI, insufficient recovery from AKI, which results in a prolonged decrease in renal function and progression to CKD, is a contributing factor to the increase in the prevalence of reduced kidney function in the elderly [23].…”
Section: Discussionmentioning
confidence: 99%